Design of an efficient magnetic brush solid acid and its catalytic use in organic reactions - Akbar Mobaraki; Mohsen Hajibeygi; Hesam Moradi; Mahdi Pirasteh; Ahmad Takallou (Scientific Reports)
Abstract In this research, with the Green Chemistry approach, to load more sulfonic acid active sites on catalyst surfaces, a nanocomposite material based on core-shell magnetite coated with vinyl silane and a sulfonated polymeric brush-like structure is designed and synthesized as a new class of efficient solid acid catalysts, referred to as Fe3O4@VS-APS brush solid acid. The synthesized catalyst was comprehensively characterized by a range of instrumental techniques, including XRD, SEM, TEM, FT-IR, EDX, TGA, and VSM. The activity of the catalyst was evaluated in Biginelli, Strecker, and esterification reactions. The Fe3O4@VS-APS brush solid acid has special features, such as easy reusability when a simple magnet is used for four reaction runs, an appropriate balance between hydrophobic and hydrophilic properties on the catalyst surface, and effective catalytic performance in the production of 3,4-dihydropyrimidin-2-one(thione) derivatives, 2-phenyl-2-(phenylamino)acetonitrile and octyl acetate.